Transparentny „белый” — rozważania o semnatyce - Narloch, Andrzej (Studia Rossica Posnaniensia, 2016)
The article describes the semantic structure of the adjective “white” in the Russian language. The author bases his analysis on R. Tokarski’s theory of two meanings of the colour white. The article formulates a hypothesis on the existence of so-called 'transparent whiteness'. His analysis uses lexicographical data taken from contemporary Russian dictionaries as well as historical data.